PENGARUH SENAM YOGA TERHADAP PENURUNAN INTENSITAS DYSMENORRHEA PADA SISWI SMA ISLAM PUJON KABUPATEN MALANG - Nadia Eva Tarinda; Rosyidah Alfitri; Widia Shofa Ilmiah (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Many women experience problems during menstruation and one of them is menstrual pain. Menstrual pain is a common condition experienced by young women who have menstruated. Dysmenorrhea can cause discomfort in daily physical activity. This study aims to analyze the effect of yoga exercise on decreased dysmenorrhea intensity before and after being given and not being given yoga exercise to Pujon Islamic High School students, Malang Regency. Methode: The research method uses a quasi-experimental approach with a pretest-posttest control group design. The research population was Pujon Islamic High School students in Malang Regency with a total sample of 32 people. Sampling used quota sampling with the Universal Pain Assessment Tool pain scale research instrument. The analysis technique uses the Wilcoxon test. Result: The results showed that almost half of the experimental group before doing yoga exercise experienced moderate pain 43.7% and after being given yoga exercise most of the pain felt mild pain 56.3% and almost half had no pain 43.7%. The control group found that almost half experienced moderate pain 43.7% and after that the pain felt was mostly mild pain 75%. The results of the Wilcoxon test obtained a p-value of 0.004 <0.05, meaning that there was an effect of yoga exercise on decreased dysmenorrhea intensity in Pujon Islamic High School students, Malang Regency. Conclusion: Yoga exercise are effective in minimizing menstrual pain in adolescents. Keywords: dysmenorrhea, yoga exercise, young women